Tandem perovskite solar cells - Rajan, Jose; Wali, Qamar; Iqbal, Yaseen; Elumalai, Naveen Kumar; Uddin, Ashraf (Elsevier, 2018)
Progress made in perovskite solar cells (PSCs) in tandem with silicon, thin films, and organic solar cells has been reviewed. Tandem configurations are comprised of two or more cells and are designed to absorb the entire range of the solar light by the successive cells. Such configurations are considered as the most sought-after remedies to generate cheaper solar electricity by increasing the efficiency beyond the theoretical limits of single junction cells. The current market leader i.e. state of the art single junction silicon solar cells have a laboratory scale efficiency ~ 25% achieved as a result of the over 60 years of research. Further research is expected to enhance their efficiency close to the theoretical limits. PSCs may be the next desired choice as the top solar cell due to its higher absorption edge (~ 2.23 eV) in comparison to its Si counterpart (~ 1.48 eV). Beginning with a brief introduction of the PSC, studies regarding its suitability for tandem devices, comparison of single and multiple junction solar cells, and the progress made so far employing different perovskite absorbers, have been reviewed. The advantages and disadvantages of PSCs, including losses of various tandem solar architectures have been discussed. Finally, the review has been concluded with a summary of the current developments and commercialization potential of this technology for real-life applications.